Identifikasi Salmonella Sp Pada Saus Cabai Pentolan yang Diperjualbelikan Di Kecamatan Mamajang Kota Makassar - Tuty Widyanti; Muawanah Muawanah; Indriany Iyonu (Lontara Journal of Health Science and Technology, 2021)
Sauce is a flavoring ingredient that is usually added to food. In the chili sauce processing process, it is possible that the raw materials used are not washed clean and the place used to store chili sauce is in the form of bottles or containers that do not undergo a sterilization process after use. One of the bacteria that contaminates chili sauce is Salmonella sp which can cause digestive tract disorders. The purpose of the study was to identify Salmonella sp in the pentolan chili sauce that was traded in the Mamajang sub-district, Makassar city, which was a laboratory observation using research methods, namely culture and biochemical tests. The research sample used was pentolan chili sauce that was traded in the Mamajang sub-district of Makassar city as many as 10 samples with the sampling technique of random sampling. Based on the research that has been done from 10 samples of pentolan chili sauce, positive results were obtained for Salmonella sp. It can be concluded that the pentolan chili sauce sold in the Mamajang district of Makassar city has been contaminated by Salmonella sp.